Effects of Consumer Antimicrobials Benzalkonium Chloride, Benzethonium Chloride, and Chloroxylenol on Colonic Inflammation and Colitis-Associated Colon Tumorigenesis in Mice. (5th March 2018) - Sanidad, Katherine Z; Yang, Haixia; Wang, Weicang; Ozay, E Ilker; Yang, Jun; Gu, Min; Karner, Emmet; Zhang, Jianan; Kim, Daeyoung; Minter, Lisa M; Xiao, Hang; Zhang, Guodong
Abstract: Benzalkonium chloride (BAC), benzethonium chloride (BET), and chloroxylenol (PCMX) are antimicrobial ingredients used in many consumer products and are frequently detected in the environment. In 2016, the U.S. Food and Drug Administration removed 19 antimicrobial ingredients from consumer antiseptic wash products, but deferred rulemaking for BAC, BET, and PCMX to allow additional time to develop new safety and efficacy data for these 3 antimicrobials. Therefore, it is important and timely to better understand the effects of these 3 compounds on human health. Here, we report that exposure to low doses of these antimicrobial compounds, in particular BAC, increases dextran sodium sulfate (DSS)-induced colonic inflammation and azoxymethane/DSS-induced colon tumorigenesis in mice. In addition, we find that exposure to BAC increases activation of Toll-like receptor 4 signaling in the systemic circulation, by disrupting intestinal barrier function and thus enhancing circulating levels of bacterial products. Together, our results suggest that these widely used antimicrobial compounds could exaggerate disease development of inflammatory bowel disease and associated colon cancer. Further studies are urgently needed to better characterize the impacts of these compounds on gut diseases.